Practice and production of teaching materials for teaching geography: a methodological proposal for school teaching from the experience in academic teaching - Silva, Daiane Alencar; Ramires, Carlos Eduardo Dourado; Souza, Gabriela Ferreira de; Amaral Neto, Vitor José Ribeiro; Mello Júnior, Valdemir Pomerening de (Revista Ensino de Geografia (Recife), 2020)
Brazilian school geography is still based on a traditional teaching model, contemplating teaching practices where the student has to decorate the content, not contributing satisfactorily to the development of critical thinking to yourself, the construction of the individual and collective being and the Society inserted. In order to break this barrier in teaching, diferente didactic and methodological proposals for the promotion of more committed classes in arouse in students the critical thinking about their daily lives. Among them, the didactic materials are important tools that help the teacher in the classroom, assisting the dynamics to the content addressed, contributing significantly for learning process to occur in a way that breaks with the model traditional yet used.Thus, this article is a proposal to contribute to the overcoming of the traditional model, aiming to present methodologies for the creation of didactic materials for the teaching of geography, from the experience academic. As methodological procedures, wehad two stages, the first one theoretical review on the topic and the second presents the elaboration of the materials developed by undergraduate academics in Geography Degree contextualizing them with the content covered